2013
DOI: 10.1186/1475-2867-13-23
|View full text |Cite
|
Sign up to set email alerts
|

RNAi silencing of c-Myc inhibits cell migration, invasion, and proliferation in HepG2 human hepatocellular carcinoma cell line: c-Myc silencing in hepatocellular carcinoma cell

Abstract: BackgroundHepatocellular carcinoma (HCC) is the most common type of liver cancer. Although much is known about both the cellular changes that lead to HCC and the etiological agents responsible for the majority of HCC cases, the molecule pathogenesis of HCC is still not well understood. We aimed to determine the effect of c-Myc gene expression on the proliferative, invasive, and migrative capabilities of hepatocellular carcinoma HepG2 cells.MethodsA plasmid- based polymerase III promoter system was used to deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…A recent report showed that knockdown of Myc suppressed proliferation of HepG2 cells (27), and we obtained results consistent with this by knockdown of Myc (data not shown), indicating that Myc expression is required for the proliferation of HepG2 cells. Thus, we studied the relevance of Skp2 to Myc in HepG2 hepatoma cells.…”
Section: Downregulation Of Skp2 With Hgf Reduces Myc Activitysupporting
confidence: 79%
“…A recent report showed that knockdown of Myc suppressed proliferation of HepG2 cells (27), and we obtained results consistent with this by knockdown of Myc (data not shown), indicating that Myc expression is required for the proliferation of HepG2 cells. Thus, we studied the relevance of Skp2 to Myc in HepG2 hepatoma cells.…”
Section: Downregulation Of Skp2 With Hgf Reduces Myc Activitysupporting
confidence: 79%
“…5A). It has previously been demonstrated that c-myc is involved in cancer cell invasion ability (Zhao et al, 2013). Our findings suggests that Ran knockdown was not sufficient to inhibit cell invasion in melanoma cells since the signalling triggered by Ran silencing through the AurkA down-regulation resulted in a stable and/or increased c-myc protein level in A375 and 526 melanoma cell lines, respectively, suggesting a c-myc-dependent and Ran-independent invasion mechanism in melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in contrast with data previously reported (Yuen et al 2013; Deng et al 2014), and suggests a secondary role for Ran in the invasive properties of melanoma. It has been recently reported that c-myc plays a key role in enhancing the invasive capability of hepatocellular carcinoma cells (Zhao et al 2013), suggesting that the increase of the 526 cell invasive capability was Ran-independent and may be c-myc-dependent, although further experiments are needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported the cooperation between c-MYC and HER2 and between c-MYC and β-CATENIN to drive mammary stem cell amplification and tumorigenesis [10, 12]. In fact, the down-regulation of c-MYC triggers the inhibition of cancer cell proliferation, invasion and migration [52]. Wnt/β-catenin signaling plays a critical role in CSCs, being β-CATENIN a key mediator of Wnt signaling [53].…”
Section: Discussionmentioning
confidence: 99%